Development of a silent air purifier and humidifier using water filter / Mohamed Fariz Nazmie Mohamed Fauzi and Raja Muhammad Aslam Raja Arif - Mohamed Fauzi, Mohamed Fariz Nazmie; Raja Arif, Raja Muhammad Aslam (School of Mechanical Engineering, 2023)
The current environmental situation is increasingly polluted with harmful gases such as carbon dioxide, resulting from various sources such as vehicles, open burning, and wildfires. These gases contribute to the rise in temperature and decrease the oxygen-gas ratio, leading to an unhealthy environment for people. Those with allergy-related issues and respiratory problems are particularly vulnerable to these adverse effects. To address this issue, the Air Purifier and Humidifier project aims to create a high-cool humidity environment that is beneficial for people's health. This project provides a low-cost and energy-saving solution to improve air quality and make people more comfortable and relaxed. The project is suitable for individuals over the age of six and is more affordable and power-efficient than standard air purifiers. In conclusion, the Air Purifier and Humidifier project provides a viable solution to overcome the harmful effects of the environment and improve people's comfort and health. This project can be implemented in various settings and is an effective way to create a healthier environment for everyone.